An ultrathin and highly efficient interlayer for lithium–sulfur batteries with high sulfur loading and lean electrolyte. Issue 14 (11th February 2022) - Fan, Xialu; Liu, Yingqi; Tan, Junyang; Yang, Shan; Zhang, Xiaoyin; Liu, Bilu; Cheng, Huiming; Sun, Zhenhua; Li, Feng
Abstract : An ultrathin and highly efficient boron nitride/single-wall carbon nanotube interlayer (UHEI) was prepared for lithium–sulfur batteries with high sulfur loading and lean electrolyte. Abstract : Lithium–sulfur (Li–S) batteries are considered to have great potential due to their high theoretical specific energy and natural abundance of sulfur. However, the practical specific energy and cycle life of Li–S pouch cells are significantly hindered by thin sulfur cathodes, flooded electrolytes and excess Li metal anodes. Here, an ultrathin and highly efficient boron nitride/single-wall carbon nanotube (BN/SWCNT) interlayer (UHEI) achieves excellent Li–S pouch cell performance with high sulfur loading and a lean electrolyte. Compared with the reported interlayer materials, the UHEI can not only hinder the diffusion of polysulfides, but also promote further redox reactions and allow Li + to pass through easily. Meanwhile, this UHEI can significantly improve lean electrolyte performance (E/S ratio of 8 μL mg −1 ) and both high and low plateau capacities of Li–S batteries with a high sulfur loading (10 mg cm −2 ). Moreover, a normalized "ratio of the areal loading interlayer to sulfur (I/S)" was proposed and two "interlayer efficiency index (IEI)" were obtained by using I/S to quantify the efficiency of interlayers at a certain current density and guide the design of high-efficiency interlayers. The IEI of our UHEI@PP is dozens of times higher than previously reported results. Li–S cells with UHEI@PP delivered a remarkable discharge capacity of 6.6 mA h cm −2 after 100 cycles at 0.2C for pouch cells (4.1 mg cm −2 per side, E/S ratio of 10 μL mg −1 ). The work provides new insights into separator modification for the practical application of lithium–sulfur batteries in the future.